Memaknai Ulang Dalil-dalil Moderasi Beragama Perspektif Qirā’ah Mubādalah - Dardiri, Ahmadi Fathurrohman (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2024)
Religious moderation appears to be frequently promoted in the context of a peaceful and nonviolent society. However, global challenges such as armed conflict and genocide in Palestine, for example, prompt the author to investigate whether the values of religious moderation (as a continuation of Islamic wasaṭiyyah or moderation) can help maintain world peace or have no influence and prestige in the face of global community. This article will investigate and re-interpret the arguments for religious moderation from the perspective of Qirā’ah Mubādalah. Mubādalah, which means ‘mutuality,’ upholds the principle of interpreting the text by presenting parties or, “...genders (which are) not mentioned in the text.” The idea is to avoid bias in interpretation due to differences in perspectives. This study uses Toshihiko Isutzu’s ‘semantic network’ theory to identify key vocabulary, including wasaṭ, the root word s-l-m and ṣulh, the attitude of doing good in the word ta̒āwun, as well as synonyms, antonyms, and an in-depth study of all key vocabulary. The results indicate that the spirit of religious moderation should not stop at the rhetorical and theoretical dialogue. Religious moderation needs to be more active, solution-oriented, and responsive to the evolution of human interactions on a regional and global scale, as well as actively responding to world imbalances through real-world actions that threaten Muslims’ existence. We have the right to actively take the initiative, both psychologically and physically, to ensure the long-term well-being of the balance of human life.